1999
DOI: 10.1108/02651339910274710
|View full text |Cite
|
Sign up to set email alerts
|

Consumer desire to buy and use products in international markets

Abstract: Focuses on two fundamental issues facing firms competing in the global arena, namely – how should executives responsible for success in international consumer markets allocate their scare marketing resources? And why, based on what methods, should they do this? Concentrating on global/pan‐European consumers in the northern European country of Finland, a quasi‐longitudinal “gap analysis” of US versus Japanese product and marketing efforts is undertaken. Using empirical evidence gathered every five years (from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As with all marketing communications outcomes, it would be very difficult to isolate the direct influence of such nation branding and positioning strategies on sales-related metrics such as foreign direct investments, tourism revenue or exports of goods and services. Nevertheless, longitudinal studies have shown that COO attitudes can indeed change over time (Wood et al, 1999). Furthermore, a study investigating the impact of hosting international events such as the Olympics on country images found that, as a respondent's media exposure to the Olympic Games increased, there were IMR 25,1 positive effects on attitudes toward electronic products made in South Korea as well as on the overall image of South Korea as a producing country (Jaffe and Nebenzahl, 1993).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…As with all marketing communications outcomes, it would be very difficult to isolate the direct influence of such nation branding and positioning strategies on sales-related metrics such as foreign direct investments, tourism revenue or exports of goods and services. Nevertheless, longitudinal studies have shown that COO attitudes can indeed change over time (Wood et al, 1999). Furthermore, a study investigating the impact of hosting international events such as the Olympics on country images found that, as a respondent's media exposure to the Olympic Games increased, there were IMR 25,1 positive effects on attitudes toward electronic products made in South Korea as well as on the overall image of South Korea as a producing country (Jaffe and Nebenzahl, 1993).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The patterns of factors showed that some attributed were more associated then other characteristics. The characteristics with high loadings indicate product competitiveness (Wood et al, 1999). Table 5 lists the factor patterns of consumer cognition of characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Tse and Gorn (1992) mentioned that country of origins had greater influences on evaluations of product qualities than brand names to consumers. Wood et al (1999) emphasized the importance of understanding the factors related to consumer preferences for characteristics associated with foreign products.…”
mentioning
confidence: 99%
“…The key points that creating distinction in advantages is derived only from goods and marketing methods that are significant to customers and the goal is to understand the stimuli of customer satisfaction and loyalty related to his willingness to consume and purchase specific foreign goods (WOOD, et al, 1999).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%